Perpustakaan Cheng Shiu University (CSU) Taiwan: Tinjauan Deskriptif - Susiana, Susiana; Wiyarsih, Wiyarsih (Media Informasi, 2024)
Libraries that aim to progress must collaborate and network with other libraries and even institutions beyond libraries. By collaborating with other libraries or institutions, many benefits can be gained. Through such collaboration, each library will be able to share information, knowledge, and skills. Collaboration is realised, among other things, by conducting visits. A direct visit to a library will provide a comprehensive overview of the visited library. This paper aims to provide a descriptive overview of the Library of the Cheng Shiu University (CSU) in Taiwan. Direct observation at the library was conducted by making a visit. The observation results show that the CSU Library is very attractive, clean, and comfortable in terms of physical appearance. Its collections and facilities are also complete, utilizing information technology, promoting the library, having creative and innovative human resources, implementing excellent services, and managing the library effectively. Based on the visit results, it can be concluded that the visit was very beneficial for the participants. Many things can be emulated and applied in the Library of the Faculty of Mathematics and Natural Sciences UGM in particular, and other university libraries in general.